Is renal abscess still a problem? - ALPAY, HARİKA; GÖKCE, İBRAHİM; SAK, MEHTAP; YILDIZ, NURDAN; ERGELEN, RABİA (MARMARA UNIV, FAC MEDICINE, 2021)
Renal abscess, the accumulation of infected fluid in the kidney, is a rare condition seen in children as well as adults. It leads to long term hospital admission and antibiotic use. Early diagnosis is an important factor in the outcome of renal abscess because the management may differ. Urinalysis test results and radiologic imaging findings of the patients who are admitted to hospital with complaints of fever, vomiting, abdominal pain or flank pain are important for the early diagnosis. Undertreated cases have high risk for renal scar formation. In this paper, we aim to present three pediatric patients, who showed the complication of renal abscess and were treated with long term antibiotic use without a need for surgical drainage.
Keywords: Urinary tract infection; Renal abscess; Children; FOCAL BACTERIAL NEPHRITIS; MEDICAL-TREATMENT; CHILDREN